Exceptio Non Adimpleti Contractus in the Sale and Purchase Agreement of a Kiosk at Baruga Market, Kendari: A Study of Hifz Al-Mal - Kusuma, Alham Jaya; Rachmadani, Rachmadani; Djaoe, Andi Novita Mudriani; Pratiwi, Arini; Muthalib, Lian Mulyani; Baso, Fatihani; Rahmawati, Rahmawati (Al-'Aqdu: Journal of Islamic Economics Law, 2025)
This study discusses the application of the principle of exceptio non adimpleti contractus in kiosk sale and purchase contracts at Baruga Market in Kendari. Exceptio non adimpleti contractus is used as a legal defense to delay or refuse the performance of obligations until the other party to the contract fulfills their obligations. Previous studies have extensively discussed this principle normatively in general contracts, but empirical studies are still limited in cases of kiosk sales and their relationship with maqasid sharia as a form of property protection in muamalah practices in traditional markets. The purpose of this study is to analyze how this principle is applied in kiosk sale and purchase contracts and to examine its compatibility with the principle of maqasid syariah, particularly hifz al-mal (protection of property). The method used was empirical legal research, where primary data was obtained from interviews and agreement documents, while secondary data was obtained from relevant literature. The results of the study show that the contract stipulated a kiosk price of IDR 80,000,000. The payment obligation has been partially fulfilled, with the buyer paying the first installment of IDR 40,000,000 but failing to pay the second installment of IDR 40,000,000. In the agreement, Article 10 stipulates that if one party violates the agreement, it shall automatically become void. The seller then used the principle of exceptio non adimpleti contractus to refuse to hand over the kiosk because his rights had not been fulfilled. From the perspective of maqasid syariah, this principle reflects the principle of hifz al-mal, which is to protect the assets of both parties by withholding the performance of obligations until the other party's obligations are fulfilled. This finding contributes to the debate on Sharia contract law by providing empirical evidence of the application of this principle in the context of traditional markets. This study recommends that contracting parties pay more attention to exception clauses and develop clear mechanisms for default